Rancang Bangun Rhodamine Detector menggunakan Metode Fuzzy Tsukamoto berbasis Internet of Things - Andayani, Ulfa; Wulandari, Eka Ratri Noor; Asriningtias, Salnan Ratih; Sutawijaya, Bayu; Rahmah, Hafrida (Universitas Merdeka Malang, 2025)
This study developed a detection device capable of identifying the presence of Rhodamine B in food using an Internet of Things (IoT)-based Fuzzy Tsukamoto method. Rhodamine B is a coloring agent commonly used in the food industry, but its presence poses health risks. The Fuzzy Tsukamoto method was applied for its ability to manage uncertain information, while IoT technology enabled real-time monitoring. The research resulted in a detection tool with high accuracy and fast response time. Based on validation using 28 field samples, the fuzzy Tsukamoto-based detection system achieved a classification accuracy of 96.5%. The integration of these technologies enhanced analytical precision and allowed direct monitoring across various food types. The findings demonstrate that the developed detection device is efficient, reliable, and compliant with food safety standards, making it suitable for use in food monitoring and quality control processes